SISTEM INFORMASI PENILAIAN KINERJA DOSEN (Studi Kasus: STEM-AKAMIGAS Cepu) - Handoyo, Joko (Jurnal Pengembangan Rekayasa dan Teknologi, 2018)
Professors profession is a profession that is very noble because it carries a very big task that can affect the progress of a nation. The advanced nation must have qualified human resources (HR) that can compete with other countries. In creating quality human resources, the role of education is very important. The role of education according to Law no. 20 of 2003 on the national education system. Performance appraisal is the determination of the operational effectiveness of an organization and its personality based on the target of predetermined strategy, standard and criteria. Lecturer performance appraisal results will produce tremendous results for the study program or faculty, especially determining the decision given rewards or sanctions, other than that the lecturer is motivated to improve its performance. Competence is a statement that describes the appearance of a certain ability unanimously which is a combination of knowledge, skills, and attitudes that can be observed and measured. Whereas with the design of the lecturer performance data management system, performance appraisal will facilitate communication between lecturers and appraisers that are done by simply entering certain data to produce monitoring information routinely and useful. Indicators that assess the main activities of pedagogic competence, personality competence and propesional competence, the value becomes a reference aspect assessed in the lecturer appraisal process. The data used is also taken from student’s idenpendensi, so that consistency is maintained.